Efficacy of albumin-bound paclitaxel versus paclitaxel in esophageal cancer: a systematic review and meta-analysis - Song, Jiayang; Xiong, Yu; Liu, Hao; Zhang, Wei; Tan, Zhongfu; Liu, Nanjiang (Frontiers in Oncology, 2025)
ObjectiveTo systematically evaluate the efficacy and safety of albumin-bound paclitaxel and paclitaxel in the treatment of esophageal cancer.MethodsSeven databases (PubMed, Cochrane Library, Embase, China National Knowledge Infrastructure, Wanfang Data, China Science and Technology Journal Database, and China Biology Medicine disc) were searched for randomized controlled trials (RCTs) of albumin-bound paclitaxel and paclitaxel in the treatment of esophageal cancer. The search was conducted from database inception to February 2025. Literature quality was assessed using the Cochrane Risk of Bias Tool version 1 (RoB 1), and the systematic review and meta-analysis was performed using RevMan 5.4.1 and STATA18.ResultsEleven RCTs were included. Meta-analysis demonstrated that albumin-bound paclitaxel significantly improved objective response rate [ORR; relative risk (RR) = 1.67, 95% confidence interval (CI) [1.45, 1.92], p < 0.001, I2 = 0%] and disease control rate (DCR; RR = 1.69, 95% CI [1.43, 1.98], p < 0.001, I2 = 0%) compared to paclitaxel. It also showed superior improvements in serum tumor markers: cancer antigen 125 (CA125) [mean difference (MD) = −1.69, 95% CI [−2.73, −0.65], p < 0.001, I2 = 83%], Carbohydrate antigen 19-9 (CA199) (MD = −2.12, 95% CI [−3.39, −0.84], p = 0.001, I2 = 85%), and carcinoembryonic antigen (CEA) (MD = −2.01, 95% CI [−2.53, −1.50], p < 0.001, I2 = 99%), although Squamous Cell Carcinoma Antigen (SCC) improvement was non-significant (MD = −1.19, 95% CI [−2.61, 0.24], p > 0.001, I2 = 100%). Regarding safety, albumin-bound paclitaxel had markedly lower incidences of diarrhea (RR = 0.49, 95% CI [0.33, 0.72], p = 0.003, I2 = 0%), nausea/vomiting (RR = 0.61, 95% CI [0.46, 0.80], p < 0.001, I2 = 0%), thrombocytopenia (RR = 0.61, 95% CI [0.44, 0.85], p = 0.004, I2 = 22%), and myalgia/arthralgia (RR = 0.45, 95% CI [0.22, 0.94], p = 0.03, I2 = 0%), while neutropenia showed no significant difference (RR = 0.58, 95% CI [0.32, 1.03], p = 0.006, I2 = 0%).ConclusionCompared to paclitaxel, albumin-bound paclitaxel (nab-paclitaxel) demonstrates superior efficacy in the treatment of esophageal cancer, with fewer adverse reactions such as diarrhea, thrombocytopenia, and musculoskeletal pain.